2019
DOI: 10.15408/ess.v9i1.12491
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Succession Planning, Transformational Leadership, Training Satisfaction Terhadap Turnover Intention Karyawan Pada Sektor Publik Kementerian Agama Jakarta Pusat

Abstract: This study tries to analyze the effect of succession planning, transformational leadership, training satisfaction on employee turnover intention in the public sector of the Central Jakarta Ministry of Religion. Responding to this study, an experiment of 120 respondents from the Central Jakarta Ministry of Religion staffing company. The sampling method uses purposive sampling and uses descriptive statistical data analysis methods (average) and multiple regression analysis. In this research, succession planning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
0
0
1
Order By: Relevance
“…Employees of 4-Star hotels in Purwokerto can still have the desire to leave the organization even though their leaders reflect a transformational spirit at work. The results of this study are in line with the research conducted Wanggi et al(2019) and (Paramita & Hendratmoko, 2021) On different objects that prove that transformational leadership styles are not in line with efforts to mitigate turnover rates directly when there are inconsistencies in leadership roles. This study had different results with (Alkarabsheh et al, 2022;Dewi & Dewi, 2020;Waskita, 2022) which found a negative effect of transformational leadership on turnover intention…”
Section: Transformational Leadership Towards Turnover Intentionsupporting
confidence: 87%
“…Employees of 4-Star hotels in Purwokerto can still have the desire to leave the organization even though their leaders reflect a transformational spirit at work. The results of this study are in line with the research conducted Wanggi et al(2019) and (Paramita & Hendratmoko, 2021) On different objects that prove that transformational leadership styles are not in line with efforts to mitigate turnover rates directly when there are inconsistencies in leadership roles. This study had different results with (Alkarabsheh et al, 2022;Dewi & Dewi, 2020;Waskita, 2022) which found a negative effect of transformational leadership on turnover intention…”
Section: Transformational Leadership Towards Turnover Intentionsupporting
confidence: 87%
“…Dampak negatif adanya perilaku turnover intention pada karyawan sangat merugikan perusahaan, karena dapat menurunkan produktivitas, motivasi, disiplin, dan moral karyawan, serta dapat meningkatkan tingkat kecelakaan kerja karena karyawan dengan perilaku turnover intention cenderung tidak fokus dalam bekerja dan tidak menggunakan seluruh kemampuannya untuk mencapai hasil kerja yang baik sehingga mengarah pada produktivitas yang lebih rendah (Suyono et al, 2020). Oleh karena itu, sangat penting bagi perusahaan untuk menerapkan strategi untuk meningkatkan retensi karyawan dan mengurangi turnover intention yang dialami oleh karyawan, terutama karyawan yang memiliki banyak kemampuan (Wanggi et al, 2019).…”
Section: Pendahuluanunclassified
“…Variabel berikut, penelitian menunjukkan bahwa shared leadership berpengaruh positif dan signifikan terhadap produktifitas kerja karyawan (Mahmud dan Sopiah, 2022;Astuty dan Udin, 2020;Athar, 2020;Rachmawati, 2018;Nurdiansyah, 2016). Hasil penelitian menunjukkan bahwa shared leadership berpengaruh negative dan tidak signifikan terhadap produktifitas kerja karyawan (Ameliana et al, 2019) Hasil penelitian menunjukkan bahwa shared leadership tidak berpengaruh terhadap produktifitas kerja karyawan (Yuwono et al, 2020;Purwanto dan Asbari, 2020).…”
Section: Pendahuluanunclassified